Cultural Orientation and Marital Quality: The Mediating Role of Gender Role Attitudes - Parsakia, Kamdin; Saadati, Nadereh (Journal of Psychosociological Research in Family and Culture, 2025)
Objective: This study aimed to investigate the relationship between cultural orientation and marital quality among Canadian married individuals, with a specific focus on the mediating role of gender role attitudes. Methods and Materials: The study employed a descriptive correlational design involving 385 married participants residing in Canada, selected using stratified random sampling based on Krejcie and Morgan’s sample size guidelines. Standardized instruments were used to assess marital quality (Dyadic Adjustment Scale), cultural orientation (Cultural Orientation Scale), and gender role attitudes (Gender Role Beliefs Scale). Data were analyzed using SPSS-27 for descriptive and correlational statistics, and AMOS-21 was used to perform structural equation modeling (SEM). Model fit was evaluated using χ²/df, GFI, AGFI, CFI, TLI, and RMSEA indices. Mediation analysis included both direct and indirect path coefficients. Findings: Pearson correlation analysis showed that marital quality was significantly related to both cultural orientation (r = .42, p < .001) and gender role attitudes (r = .48, p < .001), with a significant correlation between cultural orientation and gender role attitudes as well (r = .45, p < .001). The SEM results indicated that the model had good fit (χ²/df = 2.11, GFI = 0.94, CFI = 0.96, RMSEA = 0.053). Cultural orientation significantly predicted marital quality directly (β = 0.28, p < .001) and indirectly through gender role attitudes (β = 0.22, p < .001), confirming a partial mediating effect. Gender role attitudes also had a strong direct effect on marital quality (β = 0.49, p < .001). Conclusion: The findings underscore the critical role of cultural orientation and internalized gender role attitudes in shaping marital quality. Gender role attitudes serve as a psychological pathway through which cultural values influence relational satisfaction, emphasizing the need for culturally sensitive approaches in marital counseling and intervention.